Moving from lipids to leukocytes: inflammation and immune cells in atherosclerosis - Annink, Maxim E.; Kraaijenhof, Jordan M.; Stroes, Erik S. G.; Kroon, Jeffrey (Frontiers in Cell and Developmental Biology, 2024)
Atherosclerotic cardiovascular disease (ASCVD) is the most important cause of morbidity and mortality worldwide. While it is traditionally attributed to lipid accumulation in the vascular endothelium, recent research has shown that plaque inflammation is an important additional driver of atherogenesis. Though clinical outcome trials utilizing anti-inflammatory agents have proven promising in terms of reducing ASCVD risk, it is imperative to identify novel actionable targets that are more specific to atherosclerosis to mitigate adverse effects associated with systemic immune suppression. To that end, this review explores the contributions of various immune cells from the innate and adaptive immune system in promoting and mitigating atherosclerosis by integrating findings from experimental studies, high-throughput multi-omics technologies, and epidemiological research.